De l'utopie à la prescription de normes : les investissements politiques liés à l'apprentissage de la lecture - Sandrine Garcia (Les éditions de la Maison des sciences de l'Homme, 2013)
This work focuses on the pedagogic reforms launched in France in the 1960's and 1970's, in order to accompany the opening up of secondary education to all children. We will focus on reading learning programs which caused, at that time, numerous failures. Special attention will be given to academic and political investments on reading learning. For instance, sight-reading methods were abandoned on the ground that they did not systematically produce skillful readers. The battle for "smart" literacy learning have pushed more "modern" conceptions of reading learning on the front scene. New approaches were finally (partly) included in official curricula while sight-reading methods were more and more considered as counterproductive in learning processes. This finally opened the way to speech-language pathologists focusing on sight-reading competencies.